O level Islamiyat : yearly worked solution - Haq, Dr.Iftikharul (Lahore : Redspot publishing, 2023)
The "O Level Exam Paper Islamiyat Redspot Topical Worked Solutions (2012-2023)" is a specialized study guide for students preparing for the O-Level Islamiyat (Islamic Studies) examination. This book provides detailed, step-by-step solutions to past-year exam questions from the Singapore-Cambridge O-Level Islamiyat papers from 2012 to 2023. It is designed to help students master key Islamic studies concepts, improve their exam techniques, and boost their performance in the exam.
"Redspot Topical Worked Solutions (2012-2023)" for O-Level Islamiyat is an excellent resource for students aiming to excel in their Islamiyat exams. It provides detailed solutions to past exam questions, comprehensive coverage of the syllabus, and effective exam techniques, making it an invaluable tool for improving understanding, reinforcing knowledge, and enhancing exam performance.
Keywords: Islamiyat : Exampaper